Urban links to molt schedule, body condition and carotenoid‐based coloration in the house finch Haemorhous mexicanus. (16th March 2021) - Hutton, Pierce; McKenna, Jennifer; McGraw, Kevin J.
Abstract : Animals in urban environments are exposed to novel conditions, such as habitat and dietary alterations, and night‐time light pollution, that can shift the timing and expression of life‐history traits. Birds are popular urban‐ecological study subjects, and in these feathered animals regular plumage molt is a critical process for maintenance of feather quality and their associated functions (e.g. thermoregulation, aerodynamics and communicative coloration). We hypothesized that environmental changes associated with urbanization might affect the timing and progression of molt. As molt is energetically and nutritionally costly, we also tested whether putative urban–rural molt differences might be explained by indirect effects of urban environments on aspects of health (i.e. body condition, sexually selected plumage color). We tracked body molt intensity during molt onset, peak and completion in both sexes of urban and rural house finches Haemorhous mexicanus, and related this to body condition and sexually selected carotenoid‐based plumage coloration. We found that urban birds began molting earlier, peaked at a lower molt intensity and ended molt later than rural conspecifics. We also find that both body condition and plumage hue in males explain variation in body molt intensity differently for urban and rural populations at various points during the molting period. Overall, we demonstrate that songbird molt patterns and the development of carotenoid‐based sexual ornaments can be altered in urban environments, and that rapid urbanization may have broader implications for molt dynamics, annual life‐history traits and sexual selection.